Examining Colonial Legacies: A Postcolonial Analysis of Hanif Kureishi’s The Buddha of Suburbia (Critical Journal of Social Sciences, 2026)
Hanif Kureishi’s The Buddha of Suburbia critiques the persistence of colonial ideologies in post-imperial Britain by exploring how race, mimicry, hybridity, and performance shape immigrant identities. This paper examines how immigrant characters, particularly Karim, Haroon, and Jamila, are marginalized through racial stereotyping and forced to perform culturally exotic roles. Drawing on postcolonial theorists like Edward Said, Homi Bhabha, and Gayatri Spivak, the analysis reveals how Orientalism and mimicry constrain these characters within colonial expectations, yet also become sites of resistance and reinvention. Gender dynamics further complicate identity formation, with Jamila challenging patriarchal and colonial structures alike. Urban space, particularly London, is portrayed as a racialized landscape that reinforces power hierarchies. Ultimately, the novel argues that identity is not fixed but negotiated, shaped by both historical forces and acts of defiance. Kureishi’s narrative emphasizes the need for self-determined representation in multicultural societies still haunted by empire.